Shear deformation and grain refinement in pure Al by asymmetric rolling - 左方青 蒋建华 单爱党 方建敏 张杏耀 (Transactions of Nonferrous Metals Society of China, 2008)
Asymmetric rolling（ASR）, as one of severe plastic deformation（SPD） methods, was widely used to make ultra-fined materials with enhanced performance. Internal marks were used to show the shear deformation during asymmetric rolling with pure aluminium as a model material. Effects of reduction ratio and mismatch ratio on the shear deformation were studied. With the observed shear deformation results, equivalent strain was calculated. For lager shear deformation, rolling equipment was modified to increase friction between specimen and the rollers. Consequently, extremely fine grains with size of 500 nm are obtained in pure aluminium. With improved asymmetric rolling, the ability of grain refinement of ASR is greatly improved.